Quantitative profiling of differentially expressed oxylipins in ADSCs under proinflammatory cytokine stimulation. (30th July 2022) - Shen, Zhengze; Wang, Dan; Yu, Chaoqun; Peng, Yongbo; Cheng, Lifang; Zhang, Yuan
Abstract: Mesenchymal stem cells (MSCs) have been proved to have anti‐inflammatory capabilities, but the mechanisms are still under investigation. Recently, oxylipins have been identified as being related to the immuno‐regulation function of MSCs, but the MSC‐derived oxylipins, especially under the stimulation of versatile pro‐inflammatory cytokines, have never been comprehensively analyzed. In the present research, a UPLC–MS/MS method was employed to identify and quantify the oxylipin profiles of adipose‐derived mesenchymal stem cells (ADSCs) under cytokine stimulation (IL‐1 β, TNF‐ α, IFN‐𝛾 and TNF‐ α  + IFN‐𝛾). The differentially produced oxylipins between experimental groups were analyzed and compared. The elevated level of lipoxygenase‐15 (LOX‐15) mRNA was further verified by qRT‐PCR analysis. From the targeted 71 oxylipins, we detected and quantified 57 oxylipins, while 14 were not detected. Distinctive from other cytokines, ADSCs activated by the combination of IFN‐𝛾 and TNF‐ α up‐regulated LOX‐15 products 7‐HDHA and 15‐HEPE, which were metabolized from docosahexaenoic acid (DHA) and eicosapentaenoic acid, respectively, and involved in the pro‐resolution phase of inflammation. The results reported here make a first step towards a comprehensive characterization of MSC‐derived oxylipins under differential proinflammatory cytokine stimulation. The findings may lay a fundamental foundation for MSC‐based therapies and further determine ways to optimize the therapeutic potential of MSCs.